PENGEMBANGAN BANDUNG GIRI GAHANA GOLF & RESORT UNTUK MENINGKATKAN ATRAKSI WISATA - Fahmi Azhar Radhian, - (2009)
From now on, to keep the establish so we as a human has force to have the proactive and tolerance characteristic to the indistinctness which is happen because of the change with the highly tolerance. In this case of matter, dan say that this characteristic is the same with Bandung Giri Gahana who played as the company, not to think feeling satisfied with the product they have, and one way to solve that problem is do product development In this research, researcher uses method the descriptive method where researcher only formulate in detail without existence of more and words reduction. And to know the power and its weakness the researcher use SWOT analyzed, and the result from that is SWOT matrix and in outline of the contents are Outbound product is matching with Bandung Giri Gahana if we look from physical variable, social variable, and economic. And in the product development concept with select the game which is matchingin Bandung Giri Gahana, without change the company visionand mission before. And kind of the games can be divided into 5 category they are Ice Breaker, Team Work, Leadership, Creativity Dan High Ropes.